Examining the Relationship between Organizational Characteristics, Knowledge Management Infrastructure and Entrepreneurial Orientation with Job Communication Satisfaction - Marjan Mousavi (International Journal of Management, Accounting and Economics, 2022)
This study investigates the effect of organizational characteristics, knowledge management infrastructure and entrepreneurial orientation on job communication satisfaction in Atieh Sazan Hafez Company. The research was conducted by selecting 102 employees as the statistical sample. The analysis of the present study was performed using the structural equation modeling technique. The results of the analysis of the hypotheses indicated that organizational characteristics help positively and directly with the dimensions of knowledge management infrastructure and entrepreneurial orientation and job communication satisfaction. Efficient and motivated human resources play an important and fundamental role in increasing the effectiveness of any organization. Many factors need to be considered when it comes to human resource welfare. One of the key factors in this area is job satisfaction. Government agencies operate in a complex environment with increasing demand. In such an environment, many factors can increase or decrease people's job communication satisfaction. Today, organizations find themselves in situations where the tendency toward entrepreneurial activities is essential. Therefore, organizations should create conditions in which the atmosphere and spirit of entrepreneurship prevails and individuals can engage in entrepreneurial activities of the organization individually and in groups. Entrepreneurial orientation is a strategic advantage that is realized in the study of opportunities and organizes these affairs in order to take advantage of these opportunities.